2021
DOI: 10.1002/adem.202100831
|View full text |Cite
|
Sign up to set email alerts
|

The Improved Mechanical Anisotropy of a Commercial Al–Cu–Mg–Mn–Si (2017) Aluminum Alloy by Cross rolling

Abstract: The optimized thermomechanical process is an effective way to improve and control the properties of metallic alloys. Herein, the influence of unidirectional cold rolling and cross cold rolling on the texture and mechanical properties of a commercial Al─Cu─Mg─Mn─Si (2017) alloy is investigated. The Al sheets successfully prepared by the three cold rolling methods have different dominant texture components, and show different texture transformation routes during solution and aging treatments. In addition, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The Schmid factors of the 0 • and 90 • samples were relatively smaller, and their corresponding yield strength was much higher. Huang et al [17] observed the flake-like precipitates in an Al-Cu-Mg-Mn-Si alloy. They found that the precipitates mainly lay on the {100} planes, which indicated a remarkable orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The Schmid factors of the 0 • and 90 • samples were relatively smaller, and their corresponding yield strength was much higher. Huang et al [17] observed the flake-like precipitates in an Al-Cu-Mg-Mn-Si alloy. They found that the precipitates mainly lay on the {100} planes, which indicated a remarkable orientation.…”
Section: Introductionmentioning
confidence: 99%